Enhancing field pea productivity through varietal replacement - Singh, R K; Tripathi, Uttam Kumar; Srivastav, Veenapani (Indian Farming, 2024)
The productivity of pulse crops is decreasing in the grain bowl of the Central portion of the plateau of Bundelkhand region of Madhya Pradesh. The district, state and national productivity of field pea grain is poised at 9.81, 10.49 and 9.40q/ha against the varietal potential of 20-22 q/ha as the farmers have not adopted suitable package and practices along with improved varieties rather following their own conventional practices. In this situation, KVK Chhatarpur introduced the dual purpose improved dwarf variety of field pea (Harith-IPFD 10-12) under National Food Security Mission programme during rabi 2019-20 besides creating awareness among farmers about the balanced dose of fertilizers along with biofertilizers. Farmers adopted the improved production technology of field pea crop and received the higher grain and fresh pod production (17.8 and 80 q/ha) as well as net income (` 3990 and 71800/ha) as compared to their own traditional system of farming (8.2 & 55 q/ha and ` 6610 & 27500/ha) respectively. Moreover, cultivation of field pea crop using Harith-IPFD 10-12 along with appropriate production technology brought out the changes in social and economic status of the farmers. Similar growth was also recorded in other high economic crops owing to the technical assistance provided by the scientists of KVK at regular interval which also improved economic condition of the farmers.